2018
DOI: 10.4067/s0718-381x2018000400368
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of Conventional and Digital Methods of Obtaining Dental Impressions

Abstract: The aim of this study was to carry out a literature review on the accuracy of conventional and digital dental impression methods, as well as present the various three-dimensional intraoral scanning systems. A bibliographic search was carried out in PUBMED's main health database, in which works published between 2008 and 2018 were collected. Laboratory studies, case reports and systematic reviews were included, addressing topics that deal with conventional digital materials, impression and precision. Articles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…It was reported that experienced clinicians achieved greater homogeneity and thinner coatings. Therefore, it is recommended to use only light dusting on the surfaces to be scanned (23). In the present study, the powdering did not affect the results of the accuracy.…”
Section: Discussionmentioning
confidence: 71%
“…It was reported that experienced clinicians achieved greater homogeneity and thinner coatings. Therefore, it is recommended to use only light dusting on the surfaces to be scanned (23). In the present study, the powdering did not affect the results of the accuracy.…”
Section: Discussionmentioning
confidence: 71%
“…Lima et al [ 15 ] reported statistically significant differences by comparing the marginal adaptation of prosthetic restorations milled through both direct and indirect CAD/CAM systems in favor of the direct one. The study of Carvalho et al [ 16 ] confirmed the superiority of digital techniques in comparison with conventional methods. However, the systematic review of Goujat et al [ 17 ] reported that the marginal adaptation obtained was satisfactory without statistically significant differences between the two techniques.…”
Section: Discussionmentioning
confidence: 98%
“…But secondary areas, such as grooves and pits, were better reproduced in gypsum models. To sum up, chairside technology allows especially saving time [ 16 ] as digital scanning is easy and rapid. Besides, there is no need to disinfect and clean dental impressions either waiting cast pouring.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining a model of good quality that true to its original is extremely important for the success of the treatment; different types of materials and impression techniques have been used over the years to achieve this desired accuracy [1]. Since the introduction of dental CAD/CAM systems, the adaptation of restorations may be improved by combining intraoral scanning and digital milling [2,3].…”
mentioning
confidence: 99%